ANALISIS FINANCIAL INCLUSION TERHADAP PEMBERDAYAAN MASYARAKAT MISKIN DI MEDAN (STUDI KASUS PEMBIAYAAN MIKRO SS II DI BANK SUMUT SYARIAH) - Nasution, Hairatunnisa; Nasution, Yasir; Yafiz, Muhammad (IAIN Langsa, 2017)
This research aims to analyze the financial inclusion towards the empowerment of the poor in Medan through financing Sumut Sejahtera of the Bank Sumut Syariah. More specifically the research aims to know 1) the concept of financial inclusion that is implemented as a means of expanding access to financial services of banks and non-banks, 2) the application of the financial inclusion  Bank Sumut Syariah. Bank Sumt Syariah have significant role in the economic development of the community through a variety of financing micro, Financing of the Sumut Sejahtera. This financing facility has a lofty goal given to the community pre-prosperous society who have a business but not bankable feasibility so as to be worthy of being a customer of the bank, as well a improve people?s lives and help government programs in the framework of poverty reduction. The applicaton of financial inclusion on the financing Sumut Sejahtera of the Bank Sumut Syariah has been very clear benefits in the economic society prosper who enforce the interests for the public good. It is a basic principle in Islamic economic maqashid al-syariah. For financial inclusion theory maqashid al-syariah is one of the logical effort that must be applied as a consequence of the economic understanding of justice on one side and of religious on the other side.